2019
DOI: 10.18502/ijph.v48i5.1811
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Phylogenetic Classification of Fasciola species Isolated from Sheep and Cattle by PCR-RFLP in Zabol, in Sis-tan and Baluchistan Province, Southeast Iran

Abstract: Background: The detection of Fasciola species in various geographical regions is essential for health policymaking. Here, we aimed to identify livestock (cattle and sheep) related Fasciola genotypes by restriction fragment length polymorphism PCR. Methods: Seventy adult Fasciola flukes were collected from 70 infected livers of 35 cattle and 35 sheep slaughtered in Zabol abattoir, outh-east Iran (Jan-Jul 2017). Fasciola species were determined based on molecular features. For molecular detection, Fasciola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…The phylogenetic tree showed that the Fasciola flukes of this study were scattered as pure F. hepatica and F. gigantica clades, proposing that two genotypes of Fasciola can infect ruminants in Duhok province, these results agree with those of Shafiei et al (2014) and Mir et al (2019) in Iran. Furthermore, the present results showed the presence of a higher genetic diversity of the nuclear ITS2 sequence between F. hepatica and F. gigantica than that between them and F. nyanzea (Dinnik and Dinnik 2009) and both Fasciola species (F. hepatica and F. gigantica).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The phylogenetic tree showed that the Fasciola flukes of this study were scattered as pure F. hepatica and F. gigantica clades, proposing that two genotypes of Fasciola can infect ruminants in Duhok province, these results agree with those of Shafiei et al (2014) and Mir et al (2019) in Iran. Furthermore, the present results showed the presence of a higher genetic diversity of the nuclear ITS2 sequence between F. hepatica and F. gigantica than that between them and F. nyanzea (Dinnik and Dinnik 2009) and both Fasciola species (F. hepatica and F. gigantica).…”
Section: Resultssupporting
confidence: 92%
“…However, the results of the studies conducted by Peng et al (2009), Nguyen et al (2018), andHaridwal et al (2021) failed to distinguish between the two species of Fasciola (F. hepatica and F. gigantica) using the morphometric characters, due to the presence of intermediate forms. Furthermore, in areas where the possibility of the existence of intermediate and hybrid forms exists, it is necessary to use molecular characterization and evaluation to distinguish between species (Mir et al, 2019, Karimi, 2008, Saki and Yousefi, 2011. In this study, the adult flukes that look like hybrid forms are hardly distinguishable by morphological methods; therefore, they must be distinguished by molecular approaches as described by Ai et al (2011).…”
Section: Resultsmentioning
confidence: 99%
“…Alignment analysis revealed very close similarity among the nucleotide sequences, and genetic variation was not observed within the same species (no intraspecific variation within species) of the current study and BLAST hits in GenBank. On the other hand, significant genetic variability was detected between F. hepatica and F. gigantica, and these results agree with those of Shaldoum et al (51) and Mir et al (2), which used the same marker (ITS1) to distinguish between the two Fasciola species.…”
Section: Discussionsupporting
confidence: 91%
“…Results were also identical to those from Iran, Pakistan, India, China, Nigeria, and Kenya for F. gigantica as reported by Hamoo et al (53) in Duhok province (in Aqrah city), and also this close relationship between the same species of Fasciola has been shown by Nguyen et al (54). The analysis of the rDNA ITS1 sequence of Fasciola species was commonly reported in Asia, Europe, and African countries (2,18,49). The present study results and those of other studies demonstrate the diagnostic power of the ITS1 region in differentiating the Fasciola species (39,55).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation